Determining taxpayer compliance using tax knowledge as moderating variables - Patmawati, Efi Tri; Waluyo, Waluyo (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research is intended to determine the impact of the transformation of MSME tax rates as well as the modernization on the tax administration system on the complying to taxpayer with tax knowledge which is usually in the form of moderation variations. This research implements a quantitative approach and data collection techniques by distributing questionnaires to a number of samples that are 64 respondents with a convenience sampling method. Partial least squares (PLS) analysis was assisted by the Smart-PLS application which was used to support the research analysis, in addition to using regression analysis using the bootstrapping procedure. The results showed that changes in MSME tax rates and the modernization of the tax administration system played a significant role in taxpayer compliance. Tax understanding moderates the transformations in MSME tax rates and modernizes the tax administration system for taxpayer compliance.